(untitled) - Charan, Ram; by Ram Charan; Dominic Barton; and Dennis Carey (Boston, Massachusetts, 2018)
Typical talent-planning and HR processes are designed for predictable environments, traditional ways of getting work done, and organizations where "lines and boxes" still define how people are managed. As work and organizations have become more fluid--and business strategy is no longer about planning years ahead but about sensing and seizing new opportunities and adapting to a constantly changing environment--companies must deploy talent in new ways to remain competitive
Keywords: Manpower planning; Ability; Human capital; Business planning; Personnel departments